Heretic-erotic Alliances on Decoloniality - Ascione, Gennaro (Soft Power, 2024)
When I first met the word decolonial, I was a confused PhD student. It was 2005. For the first time I was paid a salary to study instead of paying taxes for studying; the magic of online libraries was disclosed in front of my eyes; and the journal Nepantla, views from the South mediated my encounter with Catherine Walsh and Walter Mignolo. Nepantla happened to be a major discovery about the Decolonial option within the borders of an Italian national debate where, at the time, only the name of Enrique Dussel circulated amongst small circles of theoretical and political philosophers. Nepantla existed from 2000 to 2004, therefore I met her with a sense of sudden loss, which made me even more confused than I already was. I was confused because of the pressures that the colonial capitalist mode of production imposes on intellectual workers, artists, writers, translators or creatives in general: a monster whose name is Originality.